Perancangan Dan Implementasi Model Pengembangan Entrepreneur Industri Kreatif Pada Perguruan Tinggi Berbasis Pendidikan Vokasional - Wirahadi Ahmad, Afridian; Rosalina, Eka (Akuntansi dan Manajemen, 2013)
One of the obstacles faced in the development of creative industry is related to the human resources qualification. Although the higher education is believed as the main supplier of entrepreneurs, the existing enterpreneurship course does not support the development of creative industry. Therefore, this study aims to investigate entrepreneurships characters among accounting students at the Padang State Polytechnic. This study found that majority of the students claimed that they know creative industry very well. Meanwhile, the current curriculum is more theoretical based than practical oriented. This study, therefore, suggests developing enterprenership course based on five minds of future.